Dealing with Hazards in Harmony: Participatory Mapping of Flood and Landslide Evacuation Routes in Sompok, Imogiri, Bantul, Indonesia - Malawani, Mukhamad Ngainul; Insani, Anugrah Aditya; Ardiati, Aulia Syifa; Probodani, Fatma Kusuma; Setiawan, Muhammad Anggri; Saktimulya, Sri Ratna; Sukaca, Ilham Ramadhan Putra (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2026)
This study aimed to strengthen disaster resilience in Sompok Hamlet, Imogiri, Bantul Regency, Indonesia, through the implementation of Community-Based Disaster Risk Reduction strategies. The study developed flood and landslide hazard maps using participatory mapping, field surveys, and focus group discussions and used these outputs to design evacuation routes and supporting signage for community use. The case study was situated in the post-disaster context of the 2017 Cempaka Cyclone, which triggered severe flooding and landslides in the area. The study produced a maximum flood inundation map, delineated landslide-affected zones, and identified a safe evacuation route. These maps will be very useful in improving the communities' capacity to deal with disasters in the future. The integration of the Sipendil landslide early warning system and the flood and landslide hazard maps into community-based disaster education and local tourism management is also expected to improve preparedness in Sompok. These findings provide practical evidence for localized disaster risk reduction and may offer a transferable model for similar hazard-prone communities.